Nimrod : Selected Writings. - Ekotto, Frieda (African Perspectives Ser., 2018)
The Chadian writer Nimrod-philosopher, poet, novelist, and essayist-is one of the most dynamic and vital voices in contemporary African literature and thought. Yet little of Nimrod's writing has been translated into English until now. Introductory material by Frieda Ekotto provides context for Nimrod's work and demonstrates the urgency of making it available beyond Francophone Africa to a broader global audience. At the heart of this volume are Nimrod's essays on LeI<U+00CC><U+0080><U+00CC><U+0081>„—<U+00CC><U+0081>„—<U+00CC><U+0081>™¯#x90;opold SeI<U+00CC><U+0080><U+00CC><U+0081>„—<U+00CC><U+0081>„—<U+00CC><U+0081>™¯#x90;dar Senghor, a key figure in the literary and aesthetic NeI<U+00CC><U+0080><U+00CC><U+0081>„—<U+00CC><U+0081>„—<U+00CC><U+0081>™¯#x90;gritude movement of the 1930s and president of Senegal from 1945 through 1980. Widely dismissed in recent decades as problematically essentialist, Senghorian Negritude articulated notions of "blackness" as a way of transcending deep divisions across a Black Diaspora under French colonial rule. Nimrod offers a nuanced reading of Senghor, drawing out the full complexities of Senghor's philosophy and reevaluating how race and colonialism function in a French-speaking space. Also included in this volume are Nimrod's essays on literature from the 2008 collection, The New French Matter (La nouvelle chose fran<U+00CC>ʹcaise). Representing his prose fiction is his 2010 work, Rivers' Gold (L'or des rivi<U+00CC><U+0080>eres). Also featured are some of Nimrod's best-loved poems, in both English translation and the original French. The works selected and translated for this volume showcase Nimrod's versatility, his intellectual liveliness, and his exploration of questions of aesthetics in African literature, philosophy, and linguistics. Nimrod: Selected Writings marks a significant contribution toward engaging a broader audience with one of the vital voices of our time. This book will be essential reading for Anglophone students and scholars of African philosophy, literature, poetry, and critical theory, and will offer a welcome introduction to Nimrod for general readers of contemporary international writing.